Help with linear equations

J_Barber

New member
Joined
Jun 7, 2013
Messages
17
-2[(4p+1)-(3p-1)]=5(3-p)-9
-8p-1+6p+1=15-5p-9 Remove the parentheses
-8p+6p+5p=1-1+9 Combine like terms
3p=9

p=9/3 we are required to leave our answer as an improper fraction but the answer should be 10/3

A hint as to where am I going wrong? I can not come up with the correct answer. Driving me insane!
 
Hello, J_Barber!

\(\displaystyle -2[(4p + 1) - (3p - 1)] \:=\: 5(3 - p) - 9\)

\(\displaystyle -8p \color{red}{-1} + 6p \color{red}{+ 1} \:=\: 15 - 5p - 9\;\;\;\text{ Remove the parentheses}\)
. . . This is wrong!


\(\displaystyle -2[4p + 1 - 3p + 1] \:=\:5(3-p) - 9\)

n . . . . . . .\(\displaystyle -2[p + 2] \:=\:5(3-p)-9\)

n . . . . . . . .\(\displaystyle -2p - 4 \:=\:15 - 5p - 9\)

. . . . . . . . \(\displaystyle -2p + 5p \:=\:15 - 9 + 4\)

. . . . . . . . . . . . . \(\displaystyle 3p \:=\:10\)

. . . . . . . . . . . . . . \(\displaystyle p \:=\:\frac{10}{3}\)
 
-2[(4p+1)-(3p-1)]=5(3-p)-9
-8p-1+6p+1=15-5p-9 Remove the parentheses Right here you go wrong. BE CAREFUL!!!!
-8p+6p+5p=1-1+9 Combine like terms
3p=9

p=9/3 we are required to leave our answer as an improper fraction but the answer should be 10/3

A hint as to where am I going wrong? I can not come up with the correct answer. Driving me insane!
DON'T SKIP STEPS

\(\displaystyle -2\{(4p + 1) - (3p - 1)\} = 5(3 - p) - 9 \implies\)

\(\displaystyle -2\{(4p + 1) - 3p - (-1)\} = 5(3 - p) - 9 \implies\)

\(\displaystyle -2(4p + 1 - 3p + 1) = 5(3 - p) - 9 = 15 - 5p - 9 = 6 - 5p \implies\)

\(\displaystyle -2(p + 2) = 6 - 5p \implies \)

\(\displaystyle -2p - 4 = 6 - 5p \implies\)

\(\displaystyle 5p - 2p = 6 + 4 \implies\)

\(\displaystyle 3p = 10 \implies\)

\(\displaystyle p = \dfrac{10}{3}.\)

Now CHECK.

\(\displaystyle -2\{(4p + 1) - (3p - 1)\} = -2\left\{\left(\dfrac{4 * 10}{3} + 1\right) - \left(\dfrac{3 * 10}{3} - 1\right)\right\} = -2\left(\dfrac{40 + 3}{3} - \dfrac{30 - 3}{3}\right) = -2 * \dfrac{40 + 3 - 30 + 3}{3} = -2 * \dfrac{16}{3} =\)

\(\displaystyle \dfrac{- 32}{3} = \dfrac{18 - 50}{3} = 6 + \dfrac{-50}{3} = 15 - \dfrac{50}{3} - 9 = 5\left(3 - \dfrac{10}{3}\right) - 9 = 5(3 - p) - 9.\)
 
Top